Short sickness absence and subsequent sickness absence due to mental disorders - a follow-up study among municipal employees - Hilla Sumanen; Olli Pietiläinen; Eero Lahelma; Ossi Rahkonen (BMC, 2017)
Abstract Background Mental disorders are common diagnostic causes for longer sickness absence and disability retirement in OECD-countries. Short sickness absence spells are also common, and neither trivial for health and work ability. We studied how prior short sickness absence spells and days are associated with subsequent longer sickness absence due to mental disorders in two age-groups of municipal employees during a 2-, 5- and 9-year follow-up. Methods The analyses covered 20-34 and 35-49-year-old employees of the City of Helsinki in 2004. Those with prior ≥14 day sickness absence in 2002, 2003 or 2004 were excluded. Women and men were pooled together. Short, 1-13-day sickness absence spells and days were calculated per the actual time of employment during 2004. Logistic regression analysis was used to calculate odds ratios (OR) and their 95% confidence intervals (CI) for the subsequent long (≥14 days) sickness absence due to mental disorders during three follow-ups. Results The risk for long sickness absence due to mental disorders increased with increasing amount of short sickness absence spells and days. 3 or more short sickness absence spells and 8-14 sickness absence days from short spells in 2004 were strongly associated with subsequent long sickness absence in all three follow-ups. The associations were strongest for the 2-year follow-up; the younger employees tended to have higher risks than the older ones. Conclusions Three spells or 8 days of short sickness absence per year constitutes a high risk for subsequent long sickness absence due to mental disorders and preventive measures should be considered.